Is The Wheat Futures Market Discovering Cash Prices? - Anna Szczepańska-Przekota (Communications of International Proceedings, 2022)
Mutual interactions between the agricultural commodities futures market and the spot market are one of the most important relationships that can be observed between the financial market and the real economy. The process of the flow of price impulses between these markets has long been of interest to researchers. It is important both for stock market investors and agricultural producers, as well as for decision-makers responsible for food policy. The studies conducted so far do not provide unambiguous answers about the strength and direction of flows of price impulses. This is one example of the need for continuous process monitoring. Therefore, the aim of the study was to identify the process of the flow of price impulses between the futures market and the wheat spot market. The study was carried out based on the US example. The futures prices from the CBOT exchange and the wheat producer price index were analyzed. The data covers the period between 01.2010-01.2022. The Granger causality test and the VAR model were used for the study. The results are in the minority, as a causal relationship was obtained from the spot market to the futures market, which is a less common result.
Keywords: wheat; futures; spot; causality; price transmission.